Effect of low back pain on clinical-functional factors and its associated potential risk of chronicity in adolescent dancers of classical ballet: cross-sectional study - Brenda Luciano de Souza; Patricia Colombo de Souza; Ana Paula Ribeiro (BMC, 2022)
Abstract Background Low back pain (LBP) is a common symptom in classical ballet dancers, which can limit their daily activities and dance training routines. The purpose of the study was to verify the association and comparison of clinical-functional outcomes (spine flexibility and foot posture) between different levels of intensity low back pain in adolescents of classical ballet and the potential risk of chronicity using the STarT back tool. Methods Cross-sectional study. Participants: 78 adolescent girls who practice classical ballet were evaluated and divided into groups according to level of low back pain: mild (n = 21), moderate (n = 17), and high (n = 20), and a control group (n = 20). Main outcome measures: Pain, flexibility of the spine (thoracic and lumbosacral), risk of chronicity for low back pain, and foot posture were assessed using the visual analogue scale, clinical tests, STarT back screening tool (SBST) questionnaire, and foot posture index (FPI), respectively. Results Dancers with high-intensity low back pain showed a potential risk of chronicity by the SBST. The spine pain intensity was not different considering thoracic and lumbosacral flexibility in the sagittal plane, but was different with greater supine FPI when compared to control dancers. Mild low back pain was associated with greater supine FPI. The SBST score was associated with higher exposure time-frequency and time of dancing. Conclusion Adolescents of classical ballet with high-intensity low back pain showed a potential risk of chronicity by the SBST. The level of intensity low back pain did not influence the clinical-functional aspects of spine flexibility in the sagittal plane, but the level of intensity moderate pain promoted changes in foot posture (more supinated). The potential risk of chronicity using the SBST was also associated with higher exposure time-frequency and time of dancing, in adolescents of classical ballet.